2015
DOI: 10.1111/den.12436
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of interventional endoscopic ultrasonography for the treatment of esophageal and gastric varices

Abstract: Interventional endoscopic ultrasonography (EUS) has been developed mainly for the treatment of pancreaticobiliary disorders (e.g. cyst drainage for pancreatic pseudocysts, biliary drainage for malignant biliary obstruction, and celiac plexus neurolysis). Recently, the application of interventional EUS has been expanded to a new field, the treatment of gastrointestinal varices. There have been several studies examining this new technique for the treatment of esophageal and gastric varices. In the present review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A success rate of 75% has been demonstrated for GV eradication by EUS‐guided injection of coils . Recently, one review of four studies reported the advantages for this EUS‐guided approach; however, many details remain unresolved, such as targeting of the correct vessels in cases of splenic vein hypertension associated with portal vein hypertension, targeting of the feeder vessel, and the presence of shunts. In the present study, we described the results of patients treated by EUS‐guided coil insertion with the CYA injection technique with the addition of systematic EV for GV feeder vessel evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…A success rate of 75% has been demonstrated for GV eradication by EUS‐guided injection of coils . Recently, one review of four studies reported the advantages for this EUS‐guided approach; however, many details remain unresolved, such as targeting of the correct vessels in cases of splenic vein hypertension associated with portal vein hypertension, targeting of the feeder vessel, and the presence of shunts. In the present study, we described the results of patients treated by EUS‐guided coil insertion with the CYA injection technique with the addition of systematic EV for GV feeder vessel evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of endoscopic treatment of GV was later refined with the use of EUSguidance [26,27,18,28,29] to theoretically direct injection of GV more accurately, minimize the volume of cyanoacrylate injected, target the perforating vein when possible and confirm GV eradication using Doppler examination [4]. Despite the theoretical advantages of EUS-guided fine needle injection (EUS-FNI) of cyanoacrylate over direct endoscopic injection (DEI) in the treatment of GV, currently no comparative studies exist between the two techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic ultrasonography‐guided injection sclerotherapy has been reported for the esophageal varices, 5 however, this technique is not yet a common method. This new modified endoscopic hood made esophageal EIS easier and safer.…”
Section: Brief Explanationmentioning
confidence: 99%